PENDIDIKAN KARAKTER BERBASIS NILAI KEMANUSIAAN: - Nurudin Nurudin (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Multidimensional crisis, a crisis of ethics, crisis of confidence, social confidence crisis as if will not go yet from this state. Perhaps due to stagnation and the culmination of this national issue, then appeared the discourse and practice of “character education” which seems to be a potent herb cure structural and cultural epidemic that plagues this nation. Will the character education to become “solace” of grief Indonesian nation would not go over? Is it true that a successful character education can reduce crime social, economic, political, legal, and religious? And of course there are many more questions raised related to character education urgency. In this paper, the author attempts to formulate a value-based character education as a humanitarian endeavor to overcome socio-religious conflict in Indonesia. KEY WORDS:Character Education, Religious Radicalism, Human Value, Harmony.